Comparative Analysis Of Academic Achievement Index Based On Environmental Health Products In Health Analysis - Aszrul AB; Hariyanti Haris; Sulkifliyawan (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2020)
Academic achievement is something that cannot be separated from learning activities, because learning activities are a process, while academic achievement is the output of the learning process. In achieving learning achievement, there are several factors, one of which is the person's environment, the environment is one of the factors that influence the formation and development of individual behavior, both the physical and psychological environment, including learning. The purpose of this study was to determine the Analyst Changes in the Academic Achievement Index Based on the Environment in the Health Analyst DIII Study Program at STIKES Panrita Husada Bulukumba in 2018. This type of research is descriptive with a comparative study approach. This study uses a total sampling technique with an observation sheet research instrument. The results of this study indicate that Most of the residence of DIII study program students Health analysts live more with parents than living in the dormitory, the level of achievement of DIII study program students Health analyst every year has decreased this caused by several factors, be it interests, motivations, and the place of the residence itself. Based on changes in academic achievement in semester 1 the number of respondents based on the Predicate in Health Analyst DIII Study Program found the number of respondents in Semester 1. Predicate Compliment as many as 21 respondents (27.6%), Very Satisfactory Predicate of 37 respondents (48.7%), Predicate of Satisfaction of 16 respondents (21.1%), Predicate of Unsatisfaction of 2 respondents (2.6%) In semester 2, the number of respondents based on the Predicate in Health Analyst DIII Study Program found the number of predicate respondents in Semester 2. The predicate of praise was 12 respondents (15.8%), Very Satisfactory Predicate of 25 respondents (32.9%), Predicate of Satisfaction of 24 respondents (31.6%), Predicate of Not Satisfactory 15 respondents (19.7%).